2017
DOI: 10.9758/cpn.2017.15.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and GSK3 Signaling Pathways in Bipolar Disorder: Clinical and Therapeutic Implications

Abstract: The neurobiology of bipolar disorder, a chronic and systemic ailment is not completely understood. The bipolar phenotype manifests in myriad ways, and psychopharmacological agents like lithium have long term beneficial effects. The enzyme glycogen synthase kinase 3 (GSK3) has come into focus, as lithium and several other mood stabilizing medications inhibit its activity. This kinase and its key upstream modulator, Wnt are dysregulated in mood disorders and there is a growing impetus to delineate the chief subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 51 publications
3
47
0
3
Order By: Relevance
“…Furthermore, escitalopram upregulates AKT activity by Ser473 phosphorylation [178]. The same effect as fluvoxamine [179], whereas paroxetine inhibits GSK3β via functional synergism with FK506 binding protein 51 [180]. Additionally, SSRIs regulate BDNF gene expression, which could explain a requirement of several weeks of treatment to achieve the full therapeutic effect.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Furthermore, escitalopram upregulates AKT activity by Ser473 phosphorylation [178]. The same effect as fluvoxamine [179], whereas paroxetine inhibits GSK3β via functional synergism with FK506 binding protein 51 [180]. Additionally, SSRIs regulate BDNF gene expression, which could explain a requirement of several weeks of treatment to achieve the full therapeutic effect.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…In particular, the activity of Wnt signaling is constitutively suppressed by the active form of GSK3b under basal condition (Muneer, 2017). The inactivation (phosphorylation) of GSK3b leads to dephosphorylation of b-catenin and activation of Wnt signaling to promote bone anabolism (Bertacchini et al, 2018).…”
Section: The Canonical Wingless (Wnt) Signaling Pathwaymentioning
confidence: 99%
“…Schizophrenia (SCZ) and bipolar disorder (BD) are heterogeneous psychiatric disorders that manifest during late adolescence and young adulthood, and together affect~3.5% of the US adult population [1,2]. Pharmacological, genetic, postmortem, and animal studies have linked N-methyl-D-aspartate receptor (NMDA) hypofunction [3,4], impairments in dopamine [4][5][6], winglessrelated integration site (WNT) [7,8], or calcium signaling [9], and GABAergic gene expression deficits [10][11][12][13][14][15] to SCZ and/or BD. Moreover, an increasing number of studies have reported an upregulation in non-neuronal gene expression related to inflammation in the brain of subjects with SCZ [16][17][18][19][20][21][22] and less in BD [23], such as the acute-phase inflammation marker serpin family A member 3 (SERPINA3-also known as alpha 1-antichymotrypsin) [16,19,21].…”
Section: Introductionmentioning
confidence: 99%